Healing : when a nurse becomes a patient - Brown, Theresa (Algonquin Books of Chapel Hill, 2022)
"When a cancer nurse becomes a cancer patient, she has to confront the most critical, terrified, sometimes furious patient she's ever encountered: herself. A frank look at struggling with illness while navigating the health care maze."--